2004
DOI: 10.1353/hpu.2004.0049
|View full text |Cite
|
Sign up to set email alerts
|

Providers' Perspectives and Beliefs Regarding Transition to Adult Care for Adolescents with Sickle Cell Disease

Abstract: Until recently, few children with chronic illnesses such as sickle cell disease (SCD) lived past late adolescence. Substantial reductions in mortality mean a growing number of adolescents with SCD reach adulthood. Consensus among researchers and health care providers (HCP) from multiple disciplines is that critical attention to and more empirical research on the transition from pediatric to adult care is needed. We address the following questions: (1) How do pediatric and adult providers demonstrate involvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
79
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(83 citation statements)
references
References 30 publications
1
79
1
2
Order By: Relevance
“…Contrary to our results, Telfair et al [15] found that female providers were significantly more likely to demonstrate transition. However, in their study of primary care pediatricians, Burke et al [28] also found that age, gender, and practice setting were not associated to the experiences of the pediatricians in their sample.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to our results, Telfair et al [15] found that female providers were significantly more likely to demonstrate transition. However, in their study of primary care pediatricians, Burke et al [28] also found that age, gender, and practice setting were not associated to the experiences of the pediatricians in their sample.…”
Section: Discussioncontrasting
confidence: 99%
“…Nevertheless, the literature on the domain is limited [4]: few studies exploring the opinions of adolescents and their families have been published [5][6][7][8][9][10], and research on the opinion of health professionals [6,11,12] is scarce, mostly referring to the field of pediatrics, and based on small samples. The few studies focusing on the adult physicians' point of view regarding the care of young adults with childhood chronic illness are based on samples of general internists [13] or specialists in single diseases [14,15].…”
mentioning
confidence: 99%
“…8,9 The result is that many pediatricians, youth, and families have found a limited availability of adult providers with whom to arrange a smooth transition of care. [10][11][12][13][14] In addition, evidence indicates that many adult providers feel unprepared to care for young adults with complex chronic conditions. In some cases, there is no identified adult primary care or specialty provider to whom care can be transitioned.…”
Section: Introduction and Methodologymentioning
confidence: 99%
“…7 Another article comparing providers who care for patients with sickle cell disease found that of the many potential health care providers, nurse practitioners were more likely to provide services associated with transitioning care. 8 It is unclear as to whether this is also true for additional diseases or conditions, although other articles cite nurses as being in the best position to successfully coordinate transition efforts. 7,9 Articles addressing the concerns of providers suggest that pediatricians have apprehensions regarding the care their former patients may receive in an adult care setting.…”
Section: Provider Roles and Responsibilitiesmentioning
confidence: 99%